STUDENTS’ PERSPECTIVES ON THE USE OF SEMESTA (SOURCE OF ENGLISH MATERIALS USING TECHNOLOGY-BASED APPLICATION) IN IMPROVING STUDENTS’ ENGLISH SKILLS - Dini Kurnia Irmawati; Deasy Chrisnia Natalia (Universitas Brawijaya, 2022)
This study aims to discover hospitality management students' perspectives on using SEMESTA to improve their English skills. This study used a mixed method with a quantitative and qualitative approach. The study's respondents included 35 students of Bachelor of Applied Hospitality Management, Faculty of Vocational Studies, Universitas Brawijaya. Data were collected from questionnaires and interview guidelines. The study's findings showed that the SEMESTA (Source of English Materials Using Technology-based Application) website as a medium for learning English for Hospitality Management students is easily accessible by all devices. However, there have also been instances of website buffering when respondents used the SEMESTA website. Furthermore, respondents' perspectives on English learning materials on the SEMESTA website showed that the material presented complies with their needs and is appropriately understandable. Based on the respondents’ perspectives, the English language skills that they perceived to have improved were reading and writing skills, especially for the fun grammar, reading spot, and exploration components. Utilizing the SEMESTA website as one of the English learning materials can help students learn English independently and feel the benefits of improving their English skills even though it is a gradual process. However, a number of things still need to be developed to optimize the SEMESTA website to support the English Language learning process. First, the content and variety of material on the SEMESTA website need to be improved and supplemented so that the materials are not only dominated by reading and writing exercises but also include video or listening material to help students in improving their productive speaking skills. Also, additional features need to be made to make the website look more attractive. Lastly, a login or sign-up feature must be added to identify who is accessing the website to monitor the student learning process through the SEMESTA website.